2017
DOI: 10.1038/s41598-017-15700-2
|View full text |Cite|
|
Sign up to set email alerts
|

Quasi-static and dynamic experimental studies on the tensile strength and failure pattern of concrete and mortar discs

Abstract: As concrete and mortar materials widely used in structural engineering may suffer dynamic loadings, studies on their mechanical properties under different strain rates are of great importance. In this paper, based on splitting tests of Brazilian discs, the tensile strength and failure pattern of concrete and mortar were investigated under quasi-static and dynamic loadings with a strain rate of 1–200 s−1. It is shown that the quasi-static tensile strength of mortar is higher than that of concrete since coarse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 32 publications
4
37
0
1
Order By: Relevance
“…e edges of the arcs also present a relative concentration of equivalent stress with magnitudes approximately equal to 60% and 50% of the value in the centre for angles of 20°and 30°, respectively. It can then be expected that the crack will begin in the centre and probably propagate towards the edges of the loading arc, as was observed from previous research studies [11,12,38].…”
Section: New Analytical Expression For the Brazilian Test With Loadinmentioning
confidence: 54%
“…e edges of the arcs also present a relative concentration of equivalent stress with magnitudes approximately equal to 60% and 50% of the value in the centre for angles of 20°and 30°, respectively. It can then be expected that the crack will begin in the centre and probably propagate towards the edges of the loading arc, as was observed from previous research studies [11,12,38].…”
Section: New Analytical Expression For the Brazilian Test With Loadinmentioning
confidence: 54%
“…Для новых материалов, созданных в лабораториях, потенциальное ухудшение их качества является существенным препятствием к принятию решения по их производству. Имеется широкий спектр исследований с использованием современного высокотехнологичного оборудования, касающихся деградации материалов, цель которых заключается в глубоком изучении для того, чтобы понять, как обнаружить дефекты, управлять рисками деградации матери-алов и повысить долговечность [9][10][11][12]. Для более эффективной оценки прогнозирования разрушения сложных гетерогенных материалов и формирования сопротивления материала к разрушению используют подходы фотоники [13].…”
Section: многокомпонентные материалыunclassified
“…The results showed that the flexural tensile strength is higher than split tensile strength. It is believed that the static tensile strength of mortar is higher than that of concrete, which can be attributed to that the coarse aggregates weaken the interface bonding strength of the concrete . Based on the dynamic splitting experiments of concrete, a hydrostatic‐stress‐dependent macroscopic model was suggested to strengthen the acknowledgement of strain rate on dynamic tensile behaviours of the specimens as the average strain rates as high as 10 2 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Various stress loading equipments and experimental measure methods are applied to investigate the dynamic tensile behaviours of concrete-like materials for many years. [12][13][14][15][16][17][18][19][20][21] The servo-hydraulic material testing system (MTS) is usually used at low strain rate state (<10 −1 s −1 ) and the split Hopkinson pressure bar (SHPB) system is often applied to specimen at medium strain rate (>10 1 s −1 ). 22 Experimental measure methods can be divided into two types, including direct and indirect tension testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation